Determinants of Health Care Seeking Behavior: Does Insurance Ownership Matters? - Bakar, Arpah Abu; Samsudin, Shamzaeffa (International Journal of Economics and Financial Issues, 2016)
Private health insurance has become an important health care financing mechanism. Generally, individuals purchase private health insurance to access private facilities. There is also evidence that individuals prefer private health care facilities due to perceived belief that private facilities offer better health quality and shorter waiting time. In the Malaysian context, the influence of health insurance ownership on the choice of health providers has not been explored. This paper attempts to investigate the individual health care seeking behaviors and determine the factors that influence the visit to the public and private health providers. The study employs the data from Malaysia National Health and Morbidity Survey III (2006) and 14,223 respondents are selected for this purpose. Malaysia provides new evidence from an emerging market where voluntary purchase of private health insurance co-exists with almost free public health care. Multinomial logit model is used to determine factors that influence individual choice of public and private health providers over no utilization for inpatient services. From the analysis, it is found that insurance ownership determine the likelihood of choosing private hospitals but has no influence in the choice of public health providers. The findings suggest that extending health insurance program may promote higher access to private health care facilities specifically the inpatient service. Keywords: health insurance, hospital utilization, Malaysia JEL Classification: I13